Thwarting amyloidosis: IL-17 as a disease modifier along the gut/brain axis - Wade K. Self; David M. Holtzman (The Journal of Clinical Investigation, 2025)
Recent studies have highlighted a possible role for gut microbiota in modulating Alzheimer’s disease pathology, particularly through the actions of gut-derived metabolites and their influence on the immune system. In this issue of the JCI, Chandra et al. reveal that circulating levels of the gut microbiota–derived metabolite propionate affected amyloid burden and glial activation in a mouse model of Aβ amyloidosis. The study also identifies a mechanism for the therapeutic benefit of propionate supplementation, showing that propionate lowered peripheral IL-17 and suppressed Th17 cell activity. These results support the idea of therapeutic targeting of the gut/brain/immune axis, particularly via modulation of Th17 responses, and suggest translational strategies involving microbiome-based or immunological interventions for dementia prevention and treatment.